2001
DOI: 10.2527/2001.7982202x
|View full text |Cite
|
Sign up to set email alerts
|

Complex interaction of ergovaline with 5-HT2A, 5-HT1B/1D, and alpha1 receptors in isolated arteries of rat and guinea pig.

Abstract: Vascular effects of ergovaline mediated by 5-hydroxytryptamine(HT)2A, 5-HT1B/1D, and alpha1 receptors were studied in isolated arterial preparations of rat and guinea pig. In rat tail artery ergovaline behaved as a potent contractile partial agonist showing an agonist potency (pEC50) of 8.86 +/- 0.03, a maximum response (Emax) of 59 +/- 2% with respect to 5-HT, and a partial agonist affinity (pK(P)) of 8.51 +/- 0.06. Ergovaline was equipotent with ergotamine (pEC50, 8.69 +/- 0.07; Emax, 52 +/- 4%; pK(P), 8.36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 0 publications
4
76
0
Order By: Relevance
“…Dyer (1993), Schöning et al (2001), Klotz et al (2007) and Pesqueira et al (2014) all demonstrated a very strong ligand-receptor complex for ergovaline in different vascular bioassays. This lengthy receptor occupation by ergovaline, and the like, has led to a hypothesis that ergopeptides such as ergovaline that manage to be liberated from a feedstuff, evade biotransformation by the gut microbes, succeed in traversing the epithelial basal membrane barrier of the gut and avoid hepatic detoxification or reintroduction into the gut via the biliary system can enter the peripheral tissues of the body where the ergovaline molecule can interact with any number of receptors, and because of the extended receptor binding, there is an accumulation.…”
Section: Bioaccumulation and Excretion Of Ergovalinementioning
confidence: 98%
See 3 more Smart Citations
“…Dyer (1993), Schöning et al (2001), Klotz et al (2007) and Pesqueira et al (2014) all demonstrated a very strong ligand-receptor complex for ergovaline in different vascular bioassays. This lengthy receptor occupation by ergovaline, and the like, has led to a hypothesis that ergopeptides such as ergovaline that manage to be liberated from a feedstuff, evade biotransformation by the gut microbes, succeed in traversing the epithelial basal membrane barrier of the gut and avoid hepatic detoxification or reintroduction into the gut via the biliary system can enter the peripheral tissues of the body where the ergovaline molecule can interact with any number of receptors, and because of the extended receptor binding, there is an accumulation.…”
Section: Bioaccumulation and Excretion Of Ergovalinementioning
confidence: 98%
“…These vascular effects are mediated through stimulation of various biogenic amine receptors (Berde 1980). Vasoactivity of ergovaline has been shown in the bovine uterine and umbilical arteries (Dyer 1993) and in rat-tail artery and guinea-pig iliac artery (Schöning et al 2001). Klotz et al (2007Klotz et al ( , 2008 made a direct link between ergovaline and bovine peripheral vasoconstriction using the bovine lateral saphenous-vein bioassay.…”
Section: Vasoconstrictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular dysfunction is also evidenced by in vitro findings of ergovaline induced constriction of bovine lateral saphenous veins (Klotz et al, 2006(Klotz et al, , 2007, uterine and umbilical arteries (Dyer, 1993), and rat tail and guinea pig iliac arteries (Schoning, et al, 2001). Caviceps spp.…”
Section: Wwwintechopencommentioning
confidence: 99%